Metal complexes of tridentate tripod ligands in medical imaging and therapy. (29th March 2017) - Silva, Francisco; Fernandes, Célia; Campello, Maria Paula Cabral; Paulo, António
Graphical abstract: This review highlights the most relevant chemical aspects and biological results of scorpionate-containing metal complexes with relevance for biomedical applications, namely as cytotoxic drugs, photosensitizers, CO release molecules (CORMs) or radiopharmaceuticals. Abstract: Since their development in the late 1960s, scorpionate ligands have played a great part in the design of novel compounds in the field of coordination chemistry. In this review we focus on the most relevant scorpionate-containing metal complexes that have been explored in the area of medical imaging and therapy. We intend to provide some insight into the chemistry involved in the design of these compounds, and also highlight relevant biological results that have been reported in the literature for scorpionate complexes as cytotoxic drugs, photosensitizers, CO releasing molecules (CORMs) or radiopharmaceuticals.